PENELITIAN AWAL PERANCANGAN SISTEM SMART HAND WASH ASSISTANT MENGGUNAKAN APLIKASI TINKERCAD - Alfa Satya Putra; Arnold Aribowo (Journal Information System Development (ISD), 2022)
One of the policies implemented by the government of Indonesia in order to reduce the spread of Covid-19 pandemic is the hand washing protocol. The Smart Hand Wash Assistant is designed to make use of various components that can guide the user through the hand washing procedure as described in the protocol. System design in this initial research is done in Tinkercad, which is a web-based application that can create and simulate electronic circuit designs. Testing result for ping sensor, LCD, motor and buzzer components has the success rate of 100%. Testing of the overall system shows that the Smart Hand Wash Assistant system works well in guiding the user to follow the steps of the hand washing protocol